Solution‐Focused versus Problem‐Focused Questions: Differential Effects of Miracles, Exceptions and Scales - Neipp, Marie‐Carmen; Beyebach, Mark; Sanchez‐Prada, Andrés; Delgado Álvarez, María del Carmen (Journal of family therapy, 2021)
The differential impact of solution‐focused brief therapy questions was tested. A total of 246 subjects described a personal problem they wanted to solve and were randomly assigned to one of four interventions that involved answering problem‐focused versus solution‐focused questions: a problem‐focused condition, a miracle condition, a scaling condition or an exception condition. Before and after answering the questions, participants completed measures of positive and negative affect, self‐efficacy, goal attainment, action steps and solution‐focused thinking. The miracle and exception conditions were more effective than the problem‐focused condition in reducing negative affect. The scaling condition generated more action steps than the miracle question or the exception question. These findings support solution‐focused ideas on the different effects of solution‐focused questions, but also suggest that solution‐focused and problem‐focused questions might be more similar than different in their immediate impact on clients. Practitioner points Solution‐focused and problem‐focused questions are more similar than different in their immediate impact on clients. Among solution‐focused questions, the miracle question and the exception question are more effective in reducing negative affect, and scaling questions in generating specific action steps. Integrative therapists could use solution‐focused questions not only with clients who seem more optimistic but also with less solution‐minded ones. ​ 摘要 本研究测试了聚焦解决的短期治疗问题的差异影响。共有246名受试者描述了他们想要解决的个人问题，并被随机分配到四种干预措施中的一种，这些干预措施涉及回答聚焦问题的问题和聚焦解决的问题：一个问题聚焦情境，一个奇迹情境、一个量表情境，或者一个例外情境。在回答问题前后，参与者完成了积极和消极情绪、自我效能、目标达成、行动步骤和聚焦解决式思维的量表。奇迹情境和例外情境在减少负面情绪方面比问题聚焦情境更有效。量表情境比奇迹问题或例外问题生成了更多的行动步骤。这些发现支持聚焦解决的观点，即聚焦解决的提问会产生不同效果，但也表明聚焦解决的提问和聚焦问题的提问在对来访者的直接影响方面可能相似性大于差异性。 给从业者的启示 聚焦解决的提问和聚焦问题的提问在对来访者的直接影响方面可能相似性大于差异性。 在聚焦解决的问题中，奇迹问题和例外问题在减少负面影响方面更为有效，在制定具体行动步骤方面，量表问题更为有效。 整合型的治疗师不仅可以对看似更为乐观的来访者使用聚焦解决的问题，也可以对不太具有问题解决思维的来访者使用这类问题。 Resumen Se examinó el impacto diferencial de las preguntas esenciales de terapia breve centrada en soluciones. Un total de 246 sujetos describieron un problema personal que querían resolver y fueron asignados al azar a una de las cuatro intervenciones que implicaban responder preguntas centradas en el problema versus centradas en la solución: una condición centrada en el problema, una condición de pregunta milagro, una condición de pregunta de escala o una condición de pregunta sobre excepción. Antes y después de responder las preguntas, los participantes completaron medidas de afecto positivo y negativo, autoeficacia, logro de metas, pasos de acción y pensamiento centrado en soluciones. Las condiciones de pregunta milagro y excepción fueron más efectivas que la condición centrada en el problema para reducir el afecto negativo. La condición de pregunta de escala generó más pasos de acción que la pregunta del milagro o la pregunta de excepción. Estos hallazgos respaldan las ideas centradas en soluciones sobre los diferentes efectos de las preguntas centradas en soluciones, pero también sugieren que las preguntas centradas en soluciones y centradas en problemas pueden ser más similares que diferentes en su impacto inmediato en los clientes. Puntos del practicante Las preguntas centradas en soluciones y centradas en problemas son más similares que diferentes en su impacto inmediato en los clientes. Entre las preguntas centradas en la solución, la pregunta del milagro y la pregunta de la excepción son más efectivas para reducir el afecto negativo y escalar las preguntas para generar pasos de acción específicos. Los terapeutas integradores podrían utilizar preguntas centradas en la solución no sólo con los clientes que parecen más optimistas, sino también con los menos orientados a las soluciones.